The Transparency of the Budget Cycle in Uruguay: A Process under Construction - Ponce, Matías (Revista del CLAD Reforma y Democracia, 2020)
This article aims to explore the state of budget transparency in Uruguay from a multidimensional approach that integrates visions from the specialized literature on the subject in order to understand the process of the 2015-2017 budget period. Through different research techniques, the state of the budget transparency in one of the countries with the lowest corruption rates in Latin America is reconstructed. Based on the levels of compliance with budget transparency, the document presents achievements and implementation gaps between regulations and results in this area. Finally, it outlines guidelines to be considered for the improvement of budget transparency.
Keywords: Transparency; Budget; Budget Process; Access to Information; Citizen Participation; Uruguay